PsycEXTRA Dataset 2011
DOI: 10.1037/e597922013-004
|View full text |Cite
|
Sign up to set email alerts
|

Rats answer an unexpected question after incidental encoding

Abstract: SummaryA fundamental aspect of episodic memory is that retrieval of information can occur when encoding is incidental and memory assessment is unexpected [1][2][3][4]. These features are difficult to model in animals because behavioral training likely gives rise to well-learned expectations about the sequence of events. Thus, the possibility remains that animals may solve an episodic-memory test by using well-learned semantic rules without remembering the episode at memory assessment. Here we show that rats ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Did you peck or did you refrain from pecking?" Presumably, the pigeon had to mentally travel back in time to retrieve the memory of its past behavior (see also Zhou et al, 2012, for similar results with rats). This procedure for studying episodic memory makes use of matching to sample with a transfer of training test and it suggests that pigeons can recover a memory of a past event even when unexpectedly requested to do so.…”
Section: Episodic Memorysupporting
confidence: 51%
“…Did you peck or did you refrain from pecking?" Presumably, the pigeon had to mentally travel back in time to retrieve the memory of its past behavior (see also Zhou et al, 2012, for similar results with rats). This procedure for studying episodic memory makes use of matching to sample with a transfer of training test and it suggests that pigeons can recover a memory of a past event even when unexpectedly requested to do so.…”
Section: Episodic Memorysupporting
confidence: 51%
“…Rats apparently remember the source by which information was acquired, in addition to other features of the episode (location, flavour and retrieval cue). Elsewhere we showed that source memory is hippocampal dependent [6] and that retrieval of episodic information can occur when encoding is incidental and memory assessment is unexpected [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that knowledge of the impending memory tests did not reduce the impairment of the amnesic patients on either fact or source memory, nor did it increase the relative performance of the controls. Nonetheless, the unexpected question paradigm has been regularly used by some researchers in animal cognition (Zentall et al 2001(Zentall et al , 2008Singer and Zentall 2007;Fujita et al 2012;Zhou et al 2012). …”
Section: Methods Of Assessing Episodic Memorymentioning
confidence: 99%